Pengaruh Penggunaan Teknologi Ulir Filter dan Geoisolator pada Produksi Garam Rakyat di Kabupaten Indramayu - Mutiara Salsabiela; Joko Prayitno (Jurnal Teknologi Lingkungan, 2022)
The choice of technology in the production of salt is one of the key factors to obtain higher productivity. Salt farmers in Indramayu Regency have been utilizing a combination of filtration thread technology (TUF) and Geoisolator to increase the quantity and quality of their salt production. The aim of this study was to ascertain the impact of TUF and Geoisolator utilization compared to the traditional method on salt production in Indramayu in 2015 using descriptive analysis. The result of this study shows that TUF and Geoisolator technology produces salt which met the national standard (in accordance with SNI; free from impurities and heavy metal contaminants), and higher productivity than traditional technology. The productivity of TUF and Geoisolator was ± 140 tons/ha, while that of the traditional was ± 92.23 tons/ha, or an increase of 151.8%. The selling price of salt per unit of weight increased with better salt quality. The salt price of TUF and Geoisolator was in the range of 450,000–650,000 IDR / ton (Grade I), while the traditional was in the range of 130,000–450,000 IDR / ton (Grade II). Although the investment cost of the TUF and Geoisolator was 82.2% larger than the traditional, and the operating cost also increased by 42%, the revenue from salt sales increased up to 104.7%. Thus, with higher productivity and quality, total income of salt farmers per unit of area was also higher. With higher investment cost, BEP of the TUF and Geoisolator was longer than the traditional (27 and 21 months, respectively). This result indicates that TUF and Geoisolator technology is a good alternative for improving the economy and welfare of salt farmers.